Inside Back Cover: Volume 2 Issue 1. (26th March 2021) - Gao, Mei‐Yan; Song, Bai‐Qiao; Sensharma, Debobroto; Zaworotko, Michael J.
Abstract : Inside back cover image : Adsorptive separations using porous coordination networks (PCNs) could offer an energy‐efficient alternative to current technologies for C3 hydrocarbon purification such as distillation, solvent extraction and chemical transformation. The authors herein detail how the inherent modularity of PCNs makes them amenable to crystal engineering that in turn enables exquisite control over pore size, shape and chemistry. The outcome has been highly selective binding that has enabled PCNs to serve as sorbents with benchmark performance for each of the key C3 separations. There are several distinct mechanisms that have been recognized, each of which is highlighted. The authors also discuss the major challenges and opportunities that remain to be addressed before the commercial development of PCNs as advanced sorbents for C3 separation becomes viable. (DOI: https://doi.org/10.1002/smm2.1016 )